Targeting multi-loop integrals with neural networks - Winterhalder, Ramon; Magerya, Vitaly; Villa, Emilio; Jones, Stephen; Kerner, Matthias; Butter, Anja; Heinrich, Gudrun; Plehn, Tilman (SciPost physics, 2022)
SciPost Journals Publication Detail SciPost Phys. 12, 129 (2022) Targeting multi-loop integrals with neural networks
Gesehen am 15.09.2022